MORAL VALUES IN THE NOVEL "ALMOND" BY SOHN WON PYUNG AND IMPLICATIONS IN HIGH SCHOOL LITERATURE LEARNING (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The objectives of this research are 1)Describe the moral values contained in the novel "almond" by Sohn Won-pyung2)Describe the implications contained in Sohn Won-pyung's "Almond" on literature learning.qualitative research using descriptive methods. This method is used to understand the events experienced by research subjects holistically and descriptively in the form of words related to "Moral Values in the Novel "Almond" by Sohn Won Pyung and Implications for Literature Learning”.Data collection techniques in this research were carried out by, namely (1) reading and understandingThe novel "Almond" by Sohn Won PyungOverall, in order to obtain a clear understanding of the contents of the novel, (2) record data about the moral values contained in itThe novel "Almond" by Sohn Won Pyung, (3) classify unit data related to moral valuesThe novel "Almond" by Sohn Won Pyung. Data analysis in this research was carried out using the following work steps: (1) data reduction, by selecting data that is considered important, (2) data presentation, which is an analytical presentation in the form of a description of the data with existing contextual evidence, (3) carry out verification and draw conclusions.The research results show 1. The moral values in the novel "Almond" are a. hooman's relationship with himself. In self-relationships there are (Difference, don't be a bully, friendship, prioritize family, self-acceptance, patience). b.Human Relations with other humans. In human relationships with other humans there are (mutual forgiveness, respect for others, don't be too quick to judge and enjoy gossip, empathy and caring, family strength, simplicity and happiness, diversity, struggle and perseverance. 2. The implications of the research results are moral values in the novel "Almond" by Sohn Won Pyung and its implications in studying literature in high school is that the moral values contained in the novel shape students' characters because through the novel there are various life values that occur in everyday life that should be imitated and carried out by students